Meningkatkan Kualitas dan Inovasi Produk Sebagai Strategi Pemasaran UMKM Lokal di Desa Bulakan Kecamatan Cinangka - Desma Yuliadi Saputra; Wahyuningsih Wahyuningsih; Ayu Paujiah (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy, particularly through their contributions to the formation of Gross Domestic Product (GDP) and employment absorption. MSMEs are also recognized for their strong economic resilience, making them a key pillar of national financial and economic stability. Acknowledging this significance, through the Student Community Service Program (KKM), Group 36 conducted training and mentoring for MSME actors in Bulakan Village over a two-month period. This initiative aimed to enhance the understanding of MSME actors regarding the critical impact of branding, packaging design, and product innovation on marketing strategies. The outcomes of this activity include the creation of distinctive product branding and logos, as well as innovations that have the potential to improve the quality of MSME products.